The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/pharmaceutics15102451
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomeric Membrane-Active Peptides: A Review of the Last Two Decades

Adam Carrera-Aubesart,
Maria Gallo,
Sira Defaus
et al.

Abstract: In recent decades, bioactive peptides have been gaining recognition in various biomedical areas, such as intracellular drug delivery (cell-penetrating peptides, CPPs) or anti-infective action (antimicrobial peptides, AMPs), closely associated to their distinct mode of interaction with biological membranes. Exploiting the interaction of membrane-active peptides with diverse targets (healthy, tumoral, bacterial or parasitic cell membranes) is opening encouraging prospects for peptides in therapeutics. However, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 288 publications
(361 reference statements)
0
2
0
Order By: Relevance
“…During recent years, AMPs were elaborated as anticancer peptides (ACPs) in various types of cancer . ACPs act by similar processes against cancer cells and most often disturb the structure of the phospholipid bilayer and form pores leading to cell lysis …”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…During recent years, AMPs were elaborated as anticancer peptides (ACPs) in various types of cancer . ACPs act by similar processes against cancer cells and most often disturb the structure of the phospholipid bilayer and form pores leading to cell lysis …”
Section: Resultsmentioning
confidence: 66%
“…35 ACPs act by similar processes against cancer cells and most often disturb the structure of the phospholipid bilayer and form pores leading to cell lysis. 36 In previous studies, we have already observed such effects for several sC18 variants 15,20 and, thus, elucidated the activity of the triazole-bridged peptides when in contact with cancerous HeLa cells. After incubating the cells for 24 h with various peptide concentrations, we found the highest toxicity for peptides 8A and 8B, demonstrating again their increased activity compared to the linear RL-8.…”
Section: Triazole-bridged Peptides and Their Secondarymentioning
confidence: 85%